Tra macro e micro-storia: un’analisi dell’esercizio cinematografico in provincia di Pavia, 1940-55 (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
The article focuses on the cinema history of the typical rural territory of Pavia. By using a data-driven approach resulting from an archival research, the analysis suggests the usefulness of considering a geographical framework of inquiry (on a territorial level) which can dialogue between the idiosyn- crasies of local micro-histories and broader, systematic views. For this reason, the province will be divided into its three sub-areas (Pavese, Lomellina, Oltrepò), evaluating their historical trends and local specificities. The analysis, benefitting from maps representing the cinema exhibition network, will compare two moments: the years 1940-41 and the years 1954-55.